Primary Malignant Melanoma of the Vagina - a rare and hidden diagnosis - Lopes,Ana Cláudia (2023)
Abstract Primary vaginal malignant melanomas (PVMM) are rare tumors with an incidence of 0,46/1000000 women and less than 500 cases reported in literature. The genetic patterns seem to be different from cutaneous melanomas. These tumors usually appear in women aged 60 to 70 with vaginal bleeding, discharge or a mass. It is an aggressive tumor and diagnosis is often made in advanced stages which results in low survival-rates. We present a case of a 74-year old bedridden women, with a 4 cm primary vaginal malignant melanoma. The most challenging aspect of these tumors is that no standard treatment protocol is available.